2021
DOI: 10.3390/ma14020355
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Complex Analysis of the Thermal Softening of Nitrided Layers in Tools during Hot Die Forging

Abstract: This article is devoted to the issues of thermal softening of materials in the surface layer of forging tools. The research covers numerical modeling of the forging process, laboratory tests of tempering of nitrided layers, and the analysis of tempering of the surface layer of tools in the actual forging process. Numerical modeling was supported by measuring the temperature inside the tools with a thermocouple inserted into the tool to measure the temperature as close to the surface as possible. The modeling r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Despite the fact that a direct comparison with other studies is difficult in detail due to partly unknown process boundary conditions and nitrided layer parameters, the observations from the tempering and forging experiments are examined in the following with regard to plausibility on the basis of related studies in the literature. In fact, in analogy to a study by Krawcyk et al [ 18 ], significant reductions in hardness were observed in the nitrided surface microstructure as a result of laboratory isothermal tempering tests. This study also comes to the conclusion that the start of tempering of the nitrided layer investigated can be observed from a minimum temperature of 600 °C.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Despite the fact that a direct comparison with other studies is difficult in detail due to partly unknown process boundary conditions and nitrided layer parameters, the observations from the tempering and forging experiments are examined in the following with regard to plausibility on the basis of related studies in the literature. In fact, in analogy to a study by Krawcyk et al [ 18 ], significant reductions in hardness were observed in the nitrided surface microstructure as a result of laboratory isothermal tempering tests. This study also comes to the conclusion that the start of tempering of the nitrided layer investigated can be observed from a minimum temperature of 600 °C.…”
Section: Discussionsupporting
confidence: 65%
“…Due to this, an interface has already been created in the preliminary work in order to not only reference dynamic hardness curves of the base material, but also to implement a dynamic hardness model for the nitrided layer based on the calculated wear depth [ 16 ]. Krawcyk et al already investigated the thermal softening behaviour of nitrided layers of forging tools using isothermal tempering tests and laboratory forging tests [ 18 ]. By varying the temperature between 500 °C and 700 °C for 2 h and 4 h, significant annealing effects (hardness reductions of the nitrided layers) could be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model enables a comprehensible calculation of wear locations by evaluating local contact stresses, material sliding velocity and local tool hardness [77]. While the conventional Archard model considers the tool hardness as constant, current literature agrees that cyclic thermomechanical loading to the surface leads to extensive changes of microstructure and hardness of the layer during the running production [78,79]. With regard to a data-driven modelling of this phenomenon, a test methodology was developed at the Institute of Metal Forming and Forming Machines (IFUM) to realistically replicate this load accumulation using a forming dilatometer to later analyze the resulting changes in the hardness of forging tool material [80,81].…”
Section: Tool Life Prediction In Hot Forging Determined By Digital Pr...mentioning
confidence: 99%
“…After forming 500 forged gearwheel specimens by each method, they determined that the slightest geometrical deviation was achieved with the milled die, while the most significant deviation occurred in the turned die [19]. Likewise, Krawczyk et al [20] studied surface thermal softening in forging dies. They measured surface temperatures in the order of 600 • C, which produced a softening up to a depth of 0.3 mm.…”
Section: Introductionmentioning
confidence: 99%